The police and the process of territorialization in the city of Buenos Aires. Half a century of projects, 1782-1824 (Quinto Sol, 2020)
This work focuses on analyzing the ways in which police and territory emerged together, from the urban area of the city of Buenos Aires to its suburbs, in line with the economic and political expansion that began at the end of the 18th century. It examines how the territorial divisions of Buenos Aires city were accompanied by the installation of the first police figures. The expansion of police power unfolds simultaneously with the process of miniaturization of space. For this analysis, intervened plans, police reports, agreements of the City Council of Buenos Aires, regulations and a vast bibliography are used to reconstruct the divisions of Buenos Aires territory and the location of mayors, police chiefs, mayors and lieutenants. This article argues that the process of territorialization and the institutionalization of a police device is part of half a century of projects, which begin with the Bourbon Reforms, but whose main elements are taken up by the leaders of the May Revolution and then by the reforms that put standing Bernardino Rivadavia until the mid-1820s.
Keywords: police; territoriality; space; police device